Effective approaches for early identification and proactive mitigation of aflatoxins in peanuts: An EU–China perspective. Issue 4 (31st May 2022) - Krska, Rudolf; Leslie, John F.; Haughey, Simon; Dean, Moira; Bless, Yoneal; McNerney, Oonagh; Spence, Michelle; Elliott, Chris
Abstract: Nearly 700, 000 tonnes of peanuts are consumed annually in Europe. In the last 5 years, peanuts imported from China exceeded legal European Union (EU) aflatoxin limits more than 180 times. To prevent and mitigate aflatoxin contamination, the stages of the peanut chain most vulnerable to contamination must be assessed to determine how to interrupt the movement of contaminated produce. This paper discusses effective approaches for early identification and proactive mitigation of aflatoxins in peanuts to reduce a contaminant that is an impediment to trade. We consider (i) the results of the EU Commission's Directorate‐General (DG) for Health and Food Safety review, (ii) the Code of Practice for the prevention and reduction of aflatoxins in peanuts issued by Food and Agriculture Organization/World Health Organization, (iii) the results from previous EU–China efforts, and (iv) the latest state‐of‐the‐art technology in pre‐ and postharvest methods as essential elements of a sustainable program for integrated disease and aflatoxin management. These include preharvest use of biocontrol, biofertilizers, improved tillage, forecasting, and risk monitoring based on analysis of big data obtained by remote sensing. At the postharvest level, we consider rapid testing methods along the supply chain, Decision Support Systems for effective silo management, and effective risk monitoring during drying, storage, and transport. Available guidance and current recommendations are provided for successful practical implementation. Food safety standards also influence stakeholder and consumer trust and confidence, so we also consider the results of multiactor stakeholder group discussions.